O herbicida 2,4-D afeta a estrutura da comunidade de amebas testáceas (Arcellinida e Euglyphida)?: uma abordagem experimental. - Batista, João Vitor Bredariol (2025)
Agricultural activities can carry herbicides into aquatic environments, affecting biological processes and the structure of communities. The herbicide 2,4-dichlorophenoxyacetic acid (2,4-D) is used worldwide due to its low cost and selectivity. The National Environmental Council (CONAMA) sets a maximum limit of 30 μg/L for fresh waters in Brazil. Aquatic communities have shown sensitivity to 2,4-D, with considerable changes in their diversity. Among the protists, testate amoebae are considered environmental bioindicators due to their wide distribution and rapid life cycle. However, there is still a significant gap in the study of the freshwater testate amoebae community, especially with regard to the effects of herbicides on their diversity. We investigated the effects of 2,4-D on the richness, density and composition of the testate amoeba community in artificial microcosms. It was hypothesized that increasing concentrations of the herbicide would alter the community structure. Specifically, it was expected that: i) An increase in 2,4-D would reduce richness and density over time; ii) Species composition would change with increasing 2,4-D and over time. The experiment lasted 30 days, with four treatments: i) Control, ii) 2,4-D Low (15 μg/L), iii) 2,4-D CONAMA (30 μg/L) and iv) 2,4-D High (366.6 μg/L). The results obtained indicated no direct effect of the herbicide on the structure of the testate amoebae community, with time being the main factor of variation in community structure. It is concluded that if there is any hidden effect of this compound on the testate amoebae community, it is possibly masked by changes in the community caused by temporal alterations in the physical and chemical conditions and the availability of resources in the experimental units.